2021
DOI: 10.1038/s41374-020-00523-z
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue inflammation and systemic insulin resistance in mice with diet-induced obesity is possibly associated with disruption of PFKFB3 in hematopoietic cells

Abstract: Obesity-associated inflammation in white adipose tissue (WAT) is a causal factor of systemic insulin resistance; however, precisely how immune cells regulate WAT inflammation in relation to systemic insulin resistance remains to be elucidated. The present study examined a role for 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase 3 (PFKFB3) in hematopoietic cells in regulating WAT inflammation and systemic insulin sensitivity. Male C57BL/6J mice were fed a high-fat diet (HFD) or low-fat diet (LFD) for 12 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In addition, both genes are implicated in adipose tissue dysfunction, which characterizes severe obesity. TGF-α/SMAD6 signaling is implicated in the white adipocyte commitment of mesenchymal stem cells [ 63 ] and levels of expression of PFKB3 in adipose tissue affect both inflammation and insulin sensitivity [ 64 , 65 ]. Although the current evidence suggests that epigenetic modifications of these genes might be potential markers of obesity and associated diseases, further studies are required to define their functional relevance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both genes are implicated in adipose tissue dysfunction, which characterizes severe obesity. TGF-α/SMAD6 signaling is implicated in the white adipocyte commitment of mesenchymal stem cells [ 63 ] and levels of expression of PFKB3 in adipose tissue affect both inflammation and insulin sensitivity [ 64 , 65 ]. Although the current evidence suggests that epigenetic modifications of these genes might be potential markers of obesity and associated diseases, further studies are required to define their functional relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the limited change of 4-week exercise time, the impact of relatively long exercise time on the body should be considered, which is the study we are planning to conduct in the future. In Marques' study (9), 16 weeks of moderate intensity exercise can improve the lipid status to promote the reduction of weight and obesity (10). Exercise combined with long-term LFD diet was found to reduce the weight of inguinal fat and liver inflammation significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically speaking, over-nutrition can activate the inflammatory signal pathway and release a large number of inflammatory cytokines to interfere with signal transduction, thus inducing adipose tissue (7) and liver (8) inflammation, which is a major reason for systemic insulin resistance. On the other hand, insulin resistance aggravates adipose tissue (9) and liver (10) inflammation. It leads to a vicious spiral and promotes the development of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…KDM7A [61], LMNA (lamin A/C) [62], PFKFB3 [63], NEU1 [64], DUSP22 [65], ADORA2B [66], CRTC2 [67], GRN (granulin precursor) [68], CTSD (cathepsin D) [69], IGFBP4 [70], SMYD2 [71], OSM (oncostatin M) [72], INVS (inversin) [73], ANKFY1 [74], SEMA4D [75], PPM1A [76], IFNG (interferon gamma) [77], CTBP1 [78], ATP6 [79], COX2 [80], RPS19 [81], COX1 [82] and TLK1 [83] are potential biomarkers for the detection and prognosis of renal diseases. A previous study reported that LXN (latexin) [84], LMNA (lamin A/C) [85], PFKFB3 [86], NEU1 [87], TBK1 [88], GRN (granulin precursor) [89], CTSD (cathepsin D) [90], ACADS (acyl-CoA dehydrogenase short chain) [91], IRF7 [92], S1PR1 [93], ZAP70 [94], IDH1 [95], IL15 [96], PIK3R1 [97], OSM (oncostatin M) [98], SOCS3 [99], USP21 [100], CEP19 [101], KDM2A [102], TP53 [103], BRD2 [104], ATP6 [105], BRD4 [106], COX2 [107], RPS6 [108], ND2 [109], CYTB (cytochrome b) [110] and COX1 [111] are altered expressed in obesity. Altered expression of BCL3 [112], TRAF2 [113], NEU1 [114], SNAP29 [115], AGPAT2 [116], LPCAT3 [117], ADORA2B [118], CTSD (cathepsin D) [119], ACADS (acyl-CoA dehydrogenase short chain) [120], ACAD9 [121], E4F1 [122], IRF7 [123], TAF1 [124], S1PR1 [125], RASSF1 [126], ELAC2 [127], RNF146 [128], COX15 [129], SMYD2 [130], IDH1 [131], MTO1 [132], IL15 [133], PIK3R1 [13...…”
Section: Discussionmentioning
confidence: 99%